Sublime Disembodiment? Self-as-Other in Anne Carson's Decreation - Disney, Dan (Orbis litterarum, 2012)
Anne Carson’s Decreation (2006) interrogates both the reality of the real and the possibilities for expressing glimpsed, sublime meta‐realities. The article argues that Carson reverses conventional (masculine) responses to sublime experience, and recuperates the feminine sublime as a radical, exemplary mode that removes – rather than enshrines – boundaries between the subject and immersion in the real.1